Anti‐Markovnikov Hydroamination of Aromatic Alkenes with Secondary Amines Catalyzed by Easily Accessible Yttrium Complexes. Issue 7 (1st July 2014) - Germain, Stéphane; Schulz, Emmanuelle; Hannedouche, Jérôme
Abstract Binaphthylamido alkyl yttrium complexes have been proven to promote the anti‐Markovnikov addition between various styrene derivatives and secondary amines efficiently. Although the reaction has to be performed at high temperature, it is realized advantageously with a 1:2 amine/alkene molar ratio to deliver the hydroamination product in a satisfactory isolated yield. Furthermore, the reaction with 2‐vinylpyridine proceeds at room temperature within a few minutes with a low catalyst loading of 1 mol %. The procedure has been extended to a tandem intermolecular anti‐Markovnikov–intramolecular Markovnikov hydroamination for which the chiral precatalyst delivered the targeted product in up to 85 % yield and 48 % enantiomeric excess.